The Disinformation Activities of the KGB of Lithuanian SSR and Protection of Secrets in 1954–1991 - Burinskaitė, Kristina (Genocidas ir rezistencija, 2007)
Competition between the USA and USSR during the Cold War was concurrent with spying and protection of secrets. Those targets were implemented by various measures. Disinformation was an exceptionally important method among them. This method was very complicated, secret, reaching long-term aims and therefore difficult to detect. It was used to implement propaganda, intelligent and counterintelligence tasks. There were quite a few forms of disinformation, and it was used widely. It was very important in implementing Soviet policy. Soviet ideology and circumstances of international policy determined this importance. The Soviet secret police always had a section that supervised and controlled strategically important enterprises, branches of the economy and science, transport and offices. The KGB paid much attention to them, because they were supposed to be objects of interest of foreign intelligence. A very important aspect of the KGB counterintelligence work was the protection of very important information. It also supervised how secret documents were protected in strategically important objects. A company or a plant itself (or its department) was protected. The KGB took some measures to make sure that stranger knew very little about its existence and purpose. The KGB also tried to deceive foreign intelligence by creating legends about strategic objects. The aim was to hide the true functions, the activities of the enterprises and its subordination to the military industry. Besides that, the KGB sought to protect secret information by toughening the control of movement of foreigners in Lithuania. Tourism and others exchanges with Western countries were under strict supervision of the KGB.